Formation of Information Technology in Uzbekistan - Kasimova Zumradkhan Sabirjanovna (Researchparks Publishing, 2024)
Taking into account that the development of information technology engineering is relevant today, the development and improvement of society has accelerated, the engineering task of exchanging information over the network is inevitable.